Criopreservação de grãos de pólen de espécies silvestres de Passiflora L. E revisão sistemática de quatro décadas de pesquisa - Ferreira, Michele dos Santos (2024)
Pollen, as a valuable genetic resource, plays an important role in both germplasm conservation and plant breeding. Among various conservation strategies, pollen cryopreservation stands out as an effective, innovative, and long-term strategy. This technique allows for the conservation and exchange of germplasm, plant hybridization across different locations and seasons, and overcoming flowering asynchrony, which can be a barrier to progress in breeding programs. An example is the use of wild Passiflora species, which have alleles of interest for developing improved hybrids. However, the flowering asynchrony that occurs among species can present a significant barrier to passion fruit breeding programs. Thus, this study initially aimed to establish an effective protocol for pollen cryopreservation of wild Passiflora species. To achieve this, pollen grains from eight species were dehydrated in a desiccator with silica gel and an oven (35 °C) for 0, 20, 40, and 60 minutes. They were then stored in liquid nitrogen for 24 hours. In vitro germination, pollen tube length measurements, and controlled pollination using cryopreserved pollen were evaluated. Results showed that cryopreserved pollen exhibited germination rates ranging from 71% to 28%, while fresh pollen ranged from 89% to 37%. Fruit set percentages varied from 50% to 40%, with seed germination rates between 67% and 99%. Regarding pollen tube development for cryopreserved pollen grains, a significant growth was observed compared to fresh pollen grains. These in vitro and in vivo results highlight the efficacy of cryopreservation as a robust technique for conserving haploid gene pools within a cryogenic bank. Additionally, this study also presents the first systematic review on pollen cryopreservation, encompassing 40 years of research, from the earliest studies published in 1984 to the most recent in 2024. Relevant information on this topic was compiled from five databases (Web of Science, Scopus, CABDirect, Springer, and Science Direct), using a standardized search string and predefined inclusion and exclusion criteria. A total of 566 articles were identified, of which 88 were selected for this review. These publications cover 38 plant families across 19 countries, with China, India, the United States, and Brazil as the leading research producers on this topic. This study proposed harmonizing methods and protocols to facilitate data comparison across different research centers, based on existing studies on pollen cryopreservation. In this way,this work provides a significant contribution to guiding and advancing research on the conservation of plant genetic resources.